Using dual water isotopes to quantify the mixing of water masses in the Pearl River Estuary and the adjacent northern South China Sea - Jian, Xiaoyu; Zhang, Shuwen; Lao, Qibin; Chen, Fajin; Huang, Peng; Chen, Chunqing; Zhu, Qingmei (Frontiers in Marine Science, 2022)
The mixing of different water masses is important for local physical and biogeochemical processes as well as for ecosystems in the ocean. In this study, a new dataset of stable water isotopes (δD and δ18O) combined with temperature–salinity profiles was used to quantitatively understand the mixing of water masses in the Pearl River Estuary (PRE) and the adjacent northern South China Sea (SCS). Based on hydrographic characteristics and the isotope–salinity relationships in the water column, three water masses, namely, low isotopic values (<1.5‰ for δD and <0‰ for δ18O) with a salinity of <33.20 for PRE water (PREW), high isotopic values (>2.0‰ for δD and >0.6‰ for δ18O) with a salinity of >34.60 for SCS Kuroshio Branch (SCSKB), and higher isotopic values (>3.0‰ for δD and <0.4‰ for δ18O) with a salinity of >33.30 for SCS water (SCSW), were identified in the PRE and the adjacent SCS. The mixing of the three water masses in the PRE and the adjacent SCS was mainly from SCSW (71%), followed by the SCSKB (23%), and the proportion of PREW only accounted for 6%. However, different water layers and regions are affected differently by these three water masses. The surface water is mainly influenced by the PREW, whereas the subsurface water is mainly influenced by the intrusion of SCSKB (100–300 m). The mixing process of water masses in the west side of the study area (<115°E) is mainly contributed by the SCSW (86%), whereas the contributions of PREW and SCSKB are only 4% and 10%, respectively. By contrast, the mixing of water masses in the east side (>115°E) is mainly influenced by the Kuroshio intrusion (50%). This study reveals that dual water isotopes are exquisitely sensitive to determine the complex hydrological process in the PRE and the adjacent SCS, and water masses on marine environment should deserve more attention.